The Role of Service Excellence Training for Government Employees to Improve Customer Satisfaction: Public Service Implementation in Tax Service Office in Jakarta - Handoko, Pryo (Technium Social Sciences Journal, 2021)
Improving the quality of public services is an effort to improve the quality and innovation of public services at each government agency on a regular basis according to the needs and expectations of the community. In addition, improving the quality of public services is carried out to build public trust in public service providers in order to increase public satisfaction. This research is aimed at answering the question how service excellence is implemented in the work of employees in the daily tax office, what complaints are perceived by the public regarding services they received, and how service excellence training should be provided to civil servants to improve customer satisfaction. This study proves that service excellence training for tax service office employees is very important to improve service quality so as to provide customer satisfaction.